DESIGN PROJECT ON UNDERWATER CONSTRUCTION FOR THEATRE - Nizar, N.Mohamed; Bavabahurudeen, I.; Sriram, N. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
An Immersed theatre construction technique in deep water is the latest technology and trend in the industry. The theatre is mainly constructed by improving the architectural structure at our nation and then interact the peoples by the provision of world class construction materials.The total area of the building is 3250 sq. meter it consist of 336 luxury seats with cushion effect 1x2m size seat, the total size of the theatre is 65m x 50m, and the large ticket counter and the canteens are provided.The infrastructure of the theatre is designed at dramatic look and the concrete arc type columns and beams are provided, the roofing’s are fully covered with tuff fiber glass without leakage, and it provides such a wonderful aquatic nature through this ceiling design.IS 456:2000 codes is the basic code for general construction in concrete structures, hence all the structural members are designed using limit state method in accordance with the IS 456:2000 code and design aids. The structural members are designed using HYSD rods with fe500 grade of steel and M30 grade of concrete.It is a innovative structural system, very durable and safety with good appearance .the method of limit state is used in this design. It provides wonderful entertainment and it improves the inland tourism. IJRDO